Modification in Physicochemical, Structural and Digestive Properties of Potato Starch During Heat-Moisture Treatment Combined with Microwave Pre- and Post-Treatment - Chunli Deng; Oksana Melnyk; Tatyana Marenkova; Yanghe Luo (Polish Journal of Food and Nutrition Sciences)
The objective of this study was to investigate the effects of modification by heat-moisture treatment (HMT) combined with microwave pre- and post-treatment (MW) on the physicochemical, structural and digestive properties of potato starch. The light microscopy, scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD) were used to determine the structural properties of starch. FT-IR and XRD spectra implied that MW and HMT destroyed the double helices and crystalline structure of potato starch. The relative crystallinity of modified starch granules (15.17–18.17%) was lower than that of native starch (19.39%). In the case of physicochemical properties, the modified starches had higher pasting temperature (68.8–93.0 o C) and setback viscosity (807–3168 cP), but lower peak viscosity (1315–3662 cP) and breakdown viscosity (17.3–78.3 cP) than that of native potato starch, which were 68.5 o C, 496 cP, 6598 cP and 2526 cP, respectively. The HMT and MW modifications significantly increased the content of slowly digestible starch and resistant starch. The resistant starch content of starch obtained by HMT combined with MW post-treatment was significantly higher than that of starch obtained by HMT combined with MW pre-treatment and single HMT. These results may promote good understanding of the effects of HMT combined with MW pre- and post-treatment on physicochemical properties and digestibility of potato starch, and wide utilization of microwave and heat-moisture techniques in starch modification.